The Relatıonshıp Between Wıts Appraısal And Vertıcal Dentofacıal Dımensıons And The Clınıcal Relıabılıty Of The Wıts Apprasıal - Eray Erdoğan (Galenos Yayinevi, 1996)
The evaluation of the cephalometric methods for the definition of the sagittal relation among the maxillary apical bases is saving its importance in the recent orthodontic literature. In the present study, the determination of the relation between Wits appraisal was discussed. The research was realized in two groups being sagittaly (Cl II/I) homogen, one having increased, other having normal vertical dimensions. According to the statistical analysis. Wits appraisal was significantly decreasing with the increase in the vertical dimensions, where ANB angle was increasing non significantly. It can be concluded that the change in the cant of the reference line of this appraisal (occlusal plane) is more important than the sagittal displacement of the apical bases with the augmentation of the vertical dimensions. On the other hand, the philosophic conclusions of the present study lead us to use more than one analysis to be able to interpret a cephalometric relation in a correct way.